1974
DOI: 10.1128/aac.6.4.405
|View full text |Cite
|
Sign up to set email alerts
|

Polyene-Resistant Mutants of Aspergillus fennelliae : Identification of Sterols

Abstract: Four mutants strains of Aspergillus fennelliae resistant to various polyene antibiotics have been analyzed for their sterol content. The mutant strains contained A7'22 24(2 8-ergostatrien-3#-ol and A7 22-ergostadien-3,3-ol as the major sterols, whereas the wild types contained ergosterol, indicating that the mutants contain metabolic blocks for C,-C, dehydrogenation and C24-C28 reduction in the biosynthesis of ergosterol. Revertant sectors arising from the mutant colonies contained either more A7.22-ergostadie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 14 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…A similar ergosterol content has been described in a strain of A. fumigatus which is susceptible to amphotericin B in vivo [23,24]. Polyene antifungal resistance has previously been attributed to lesions in the ergosterol biosynthetic pathway in clinical isolates of Candida albicans [22,25,26] and Cryptococcus neoformans [27] and in laboratory mutants of C. albicans [22,28], A. fennelliae [29] and of a protozoan, Leishmania donovani [30]. Nevertheless, amphotericin B resistance has also been reported in C. albicans [31], Cr.…”
Section: Discussionmentioning
confidence: 79%
“…A similar ergosterol content has been described in a strain of A. fumigatus which is susceptible to amphotericin B in vivo [23,24]. Polyene antifungal resistance has previously been attributed to lesions in the ergosterol biosynthetic pathway in clinical isolates of Candida albicans [22,25,26] and Cryptococcus neoformans [27] and in laboratory mutants of C. albicans [22,28], A. fennelliae [29] and of a protozoan, Leishmania donovani [30]. Nevertheless, amphotericin B resistance has also been reported in C. albicans [31], Cr.…”
Section: Discussionmentioning
confidence: 79%
“…These are ineffective against Pneumocystis carinii, which has cholesterol instead of ergosterol [38]. The emergence of polyene resistant fungi due to the presence of sterols other than ergosterol in their membranes has also been reported [39][40][41][42].…”
Section: Mode Of Actionmentioning
confidence: 99%
“…Different approaches have demonstrated that mutants resistant to AMB have reduced ergosterol content (74)(75)(76)(77)(78)(79)(80)(81)(82). In contrast, resistance to AMB has also been reported in isolates without any ergosterol defect (83)(84)(85).…”
Section: Discussionmentioning
confidence: 99%